2014
DOI: 10.1080/09593330.2014.886627
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of mercury from water by modified multi-walled carbon nanotubes: adsorption behaviour and interference resistance by coexisting anions

Abstract: This investigation reports the use of modified multi-walled carbon nanotubes (MWCNTs) with various functional groups for adsorbing inorganic divalent mercury (Hg(II)) from water samples. To elucidate the behaviours and mechanisms of Hg(II) adsorption by modified MWCNTs, their adsorption capacity was studied by considering adsorption isotherms and kinetics. Particular attention was paid to interference of coexisting inorganic ions with Hg(II) adsorption. The results reveal that functionalization with oxygen-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…High concentration of Cl − in solution could also promote the formation of very stable MeHgCl complex which showed lower sorption than MeHg to MWCNTs. These results agreed with those of previous studies [20,48]. de Diego et al [48] found that a high concentration NaCl could led to declined adsorption rates of mercury species.…”
Section: Effect Of CL − On Adsorptionsupporting
confidence: 83%
See 4 more Smart Citations
“…High concentration of Cl − in solution could also promote the formation of very stable MeHgCl complex which showed lower sorption than MeHg to MWCNTs. These results agreed with those of previous studies [20,48]. de Diego et al [48] found that a high concentration NaCl could led to declined adsorption rates of mercury species.…”
Section: Effect Of CL − On Adsorptionsupporting
confidence: 83%
“…Figure 3 also shows that for pristine MWCNTs, MWCNTs-OH and MWCNTs-COOH, the removal efficiency of Hg 2+ and MeHg decreased gradually with the increase of pH. This is because with the increase of solution pH, the Hg(OH) + or MeHgOH compounds could be generated, which is stable in the water and reduced the Hg 2+ and MeHg adsorption [17,20]. It should be noted that a slight increase of removal efficiency of Hg 2+ and MeHg were observed for pH > 8.0.…”
Section: Ftir Spectroscopic Characterization Of Mwcntsmentioning
confidence: 79%
See 3 more Smart Citations